The mouse intron-nested gene, Israa, is expressed in the lymphoid organs and involved in T-cell activation and signaling. (July 2019) - Ben Khalaf, Noureddine; Al-Mashoor, Wedad; Saeed, Azhar; Al-Mehatab, Dalal; Taha, Safa; Bakhiet, Moiz; Fathallah, M. Dahmani
Highlights: The Zmiz1 intron-nested gene Israa, is expressed in CD3 + T-cells during all developmental stages in the thymus. Expression regulation of Israa and its host gene Zmiz1 is dissociated. Israa is downregulated during T-cell activation. ISRAA interacts with ELF-1 and regulates gene expression in T-cells. Abstract: We have previously reported Israa, immune-system-released activating agent, as a novel gene nested in intron 8 of the mouse Zmiz1 gene. We have also shown that Israa encodes for a novel FYN-binding protein and might be involved in the regulation of T-cell activation. In this report, we demonstrate that Israa gene product regulates the expression of a pool of genes involved in T-cell activation and signaling. Real time PCR and GFP knock-in expression analysis showed that Israa is transcribed and expressed in the spleen mainly by CD3 + CD8 + cells as well as in the thymus by CD3 + (DP and DN), CD4 + SP and CD8 + SP cells at different developmental stages. We also showed that Israa is downregulated in T-cells following activation of T-cell receptor. Using yeast two-hybrid analysis, we identified ELF1, a transcription factor involved in T-cell regulation, as an ISRAA-binding partner. Transcriptomic analysis of an EL4 cell line overexpressing ISRAA revealed differential expression of several genes involved in T-cell signaling, activation and development. Among these genes, Prkcb, Mib2, Fos, Ndfip2, Cxxc5, B2m, Gata3 and Cd247 were upregulated whereas Itk, Socs3, Tigit, Ifng, Il2ra and FoxJ1 were downregulated. Our findings support the existence in mouse of a novel FYN-related T-cell regulation pathway involving the product of an intron-nested gene.